Proposta de uma sequência didática com o uso de recursos diversificados para o ensino e aprendizagem de tópicos específicos de astronomia - Moreira, Raphael Henrique (Universidade Federal de São Carlos, 2015)
The current challenges of the Brazilian education are given in different planes, are those related to structural conditions, a real recognition of the importance of teacher and their training, and the pedagogical innovation. This latter aspect involves rethinking approaches and resources used in teaching. Considering this, in this work was prepared a didactic sequence intended to help improve the teaching and learning of a specific science theme related to the topic Earth and Universe: location by visible stars in the sky. This theme includes what is suggested in the National Curriculum Parameters and in the curriculum of the São Paulo state for students of the 7th graders of elementary school. The didactic sequence was planned using some principles contained in the Potentially Significant Teaching Units (UEPS), in the Teaching-Learning sequences (TLS) and in problem situations. The educational product was created to articulate various teaching resources, some already available for students of the public school of São Paulo, and others built in this work, as a Board Game and a model for the construction of Southern Cross Constellation. The didactic sequence was applied in a class of 7th graders of a elementary public school in São Paulo, i.e., in a real environment of education. As a result of the implementation, it was observed that some activities of the SD contributed to fulfill of requirements necessary for there to meaningful learning: the student predisposition for learning and the availability of potentially significant materials.
Proposal for a teaching sequence with the use of diverse resources for teaching and learning of specific topics of astronomy
Keywords: Ensino fundamental; Constelações; Sequência didática; Unidades de ensino potencialmente significativas; Sequência de ensino e aprendizagem; Elementary school; Constellations; Didactic sequence; Potentially significant teaching units; Teaching-learning sequences; CIENCIAS EXATAS E DA TERRA